2007
DOI: 10.1007/s10735-007-9134-1
|View full text |Cite
|
Sign up to set email alerts
|

The spatio-temporal expression pattern of cytoplasmic Cu/Zn superoxide dismutase (SOD1) mRNA during mouse embryogenesis

Abstract: The cytoplasmic Cu/Zn-superoxide dismutase (SOD1) represents along with catalase and glutathione peroxidase at the first defense line against reactive oxygen species in all aerobic organisms, but little is known about its distribution in developing embryos. In this study, the expression patterns of SOD1 mRNA in mouse embryos were investigated using real-time RT-PCR and in situ hybridization analyses. Expression of SOD1 mRNA was detected in all embryos with embryonic days (EDs) 7.5-18.5. The signal showed the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…SOD1 plays a major role in antioxidant defense by converting O 2- to H 2 O 2 and water [15]. Recently, we demonstrated that SOD1 transcripts were present at all embryonic stages [30]. Here, we confirm the expression pattern of SOD1 protein during normal embryonic development.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…SOD1 plays a major role in antioxidant defense by converting O 2- to H 2 O 2 and water [15]. Recently, we demonstrated that SOD1 transcripts were present at all embryonic stages [30]. Here, we confirm the expression pattern of SOD1 protein during normal embryonic development.…”
Section: Discussionsupporting
confidence: 82%
“…Co-treatment with SOD alleviated the teratogenicity of a broad range of embryonic cytotoxic agents, including ethanol and hyperglycemia [3,29]. SOD1 mRNA was detected in all embryos at embryonic day (ED) 7.5-18.5 and was expressed in a cell- and tissue-specific manner in developing organs [30]. In this study, we investigated the expression patterns of SOD1 protein during embryonic development, using Western blotting and immunohistochemical analysis, to better understand the function of SOD1 in embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that antioxidant enzymes, including GPx1 and superoxide dismutase 1, were expressed throughout all mouse embryonic stages (Baek et al, 2005;Yon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial expression patterns were determined by whole mount in situ hybridization (Baek et al, 2005;Yon et al, 2008) using a DIG-labelled antisense probe. An antisense probe for the in situ hybridization was transcribed with T7 from the full length cDNA in the original pGEM-T vector digested with Spe I (sense: SP6).…”
Section: Preparation Of Probe and In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation